2012
DOI: 10.1177/0022022111435097
|View full text |Cite
|
Sign up to set email alerts
|

Biculturalism and Adjustment

Abstract: Biculturalism (having two cultures) is a growing social phenomenon that has received considerable attention in psychology in the last decade; however, the issue of what impact (if any) biculturalism has on individuals' adjustment remains empirically unclear. To answer this question, we conducted a meta-analysis that included 83 studies, 322 rs, and 23,197 participants. Results based on the random-effects approach show a significant, strong, and positive association between biculturalism and adjustment (both ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

63
680
8
18

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 846 publications
(769 citation statements)
references
References 170 publications
63
680
8
18
Order By: Relevance
“…More positive health outcomes are typically seen when people can both maintain a connection with their culture of origin and adopt aspects of the new culture (Abbott et al, 2003; Berry, 1997; Williams & Berry, 1991). Indeed, meta-analytical evidence from 83 studies with more than 20,000 participants has shown that integration (i.e., holding on to both cultures) is associated with better well-being outcomes and socio-cultural adaptation (Nguyen & Benet-Martinez, 2013). However, for the reasons suggested above, integration is not easy for many older adults.…”
mentioning
confidence: 99%
“…More positive health outcomes are typically seen when people can both maintain a connection with their culture of origin and adopt aspects of the new culture (Abbott et al, 2003; Berry, 1997; Williams & Berry, 1991). Indeed, meta-analytical evidence from 83 studies with more than 20,000 participants has shown that integration (i.e., holding on to both cultures) is associated with better well-being outcomes and socio-cultural adaptation (Nguyen & Benet-Martinez, 2013). However, for the reasons suggested above, integration is not easy for many older adults.…”
mentioning
confidence: 99%
“…В работе A.M.D. Nguyen и V. Benet-Martinez [37] на основе ме-та-анализа 83 исследований представителей мигран-тов и этнических меньшинств было установлено, что стратегия интеграции позитивно взаимосвязана с психологической и социокультурной адаптацией.…”
unclassified
“…Given the spread of globalisation and ease of long-distance travel and communication, immigration nowadays has become less a clear break from home and more a form of living and working in which transnational connectivity between destination and home plays an increasingly prominent role (Dahinden, 2009;Vertovec, 1999). The model of transnational bicultural place to be developed below captures this modern transnational element as compared to earlier models that focus only on social networks in the place of residence (Nguyen & Benet-Martínez, 2013). Applying the model to Hong Kong Chinese immigrants in Britain, who are a significant part of the British ethnic minority population (Office for National Statistics, 2009), the present study offers a fuller account of the impact of immigrants' overall social networks on their dual cultural self-concepts (i.e.…”
mentioning
confidence: 99%